2010
DOI: 10.1016/j.enpol.2009.08.040
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of battery electric, hydrogen fuel cell and hybrid vehicles in a future sustainable road transport system

Abstract: This is a pre-print version of: Offer, G.J., et al., Comparative analysis of battery electric, hydrogen fuel cell and hybrid vehicles in a future sustainable road transport system. Energy Policy (2009Policy ( ), doi:10.1016Policy ( /j.enpol.2009 AbstractThis paper compares battery electric vehicles (BEV) to hydrogen fuel cell electric vehicles (FCEV) and hydrogen fuel cell plug-in hybrid vehicles (FCHEV). Qualitative comparisons of technologies and infrastructural requirements, and quantitative comparisons of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
219
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 469 publications
(250 citation statements)
references
References 11 publications
2
219
0
2
Order By: Relevance
“…Examining the future cost trajectories of EV battery packs, Cluzel and Douglas (2012) find that, by 2030, costs of production have the potential to decrease to $215 per kilowatt hour with similar estimates noted by Offer et al (2010) who found that, by 2030, EVs have the potential to exhibit significantly lower lifecycle costs compared to conventional internal combustion engine vehicle.…”
Section: Past Researchmentioning
confidence: 55%
“…Examining the future cost trajectories of EV battery packs, Cluzel and Douglas (2012) find that, by 2030, costs of production have the potential to decrease to $215 per kilowatt hour with similar estimates noted by Offer et al (2010) who found that, by 2030, EVs have the potential to exhibit significantly lower lifecycle costs compared to conventional internal combustion engine vehicle.…”
Section: Past Researchmentioning
confidence: 55%
“…Figure 5 shows the resulting approximate equivalent CO 2 emissions in rank order from least to most with the results summarised in Table 4. Produced from steam reformed natural gas according to assumptions in (Offer, 2010) …”
Section: Co 2 Emissionsmentioning
confidence: 99%
“…Is this an attainable target for hydrogen? Offer et al [21] report predictions of the cost of hydrogen vehicles in 2010 and 2030, compared to battery electric and conventional (gasoline) vehicles. We follow their lead in concentrating on a hybrid hydrogen-electric vehicle, in which a battery is used to aid short-term acceleration, thus economising on the size of fuel cell required, and hydrogen is used at cruising speed, thus economising on the size of battery needed.…”
Section: Hydrogen Break-evenmentioning
confidence: 99%
“…1 An anonymous referee has pointed out that a hydrogen economy could also use hydrogen in internal combustion engines, with somewhat lower efficiency but negating any problems in developing fuel cells. Source: derived from data in [21] All three of the break even distances (obtained by dividing the difference in capital costs by the difference in running cost per km) are below the critical level of around 40,000 km. However, we should consider the possibility that hydrogen vehicles develop less slowly than expected, or that the price of gasoline rises by less.…”
Section: Hydrogen Break-evenmentioning
confidence: 99%